Analisis Pendapatan Usaha Peternak Sapi Potong Sistem Intensif di Desa Sukarame Kecamatan Sukarame Kabupaten Tasikmalaya - Salim; Ajeng Sabarini Muslimah; Ikhsan Fauzan Nuzaba (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
Sukarame Village is one of the 6 villages in the Sukarame District, Tasikmalaya Regency, this village is a village that is in a strategic location. In terms of economic conditions, seeing that the area is still beautiful filled with rice fields, gardens, mountains, almost 55% of the population works as farmers and ranchers. In Sukarame Village there are 2 livestock businesses in the form of beef cattle which use an intensive system, namely Nyencang and Cantilan farms, these farms have been established for more than 4 years. The formulation of the problem in this study is how the income of beef cattle breeders with an intensive system in Sukarame Village, using a descriptive quantitative method. This study describes the amount of income earned by beef cattle business actors in Sukarame Village. The data analysis used is to calculate the income from the sale of cattle per head during the maintenance period of each breeder, and compile the data. The results of the research that has been done show that the income of farmers in the intensive beef cattle breeding business in Sukarame Village on the Nyencang farm is Rp. 2,458,300/ head for 6 months of maintenance and on Cantilan farms Rp. 3,044,915/head for 1 year of maintenance. The existence of these differences is caused by the maintenance period and the different types of livestock owned in running their business.